Pengaruh Air Rebusan Daun Seledri pada Lansia Penderita Hipertensi di Puskesmas Rusip Provinsi Aceh Tahun 2022 - Linawati Linawati; Kamelia Sinaga; Imran Saputra Surbakti; Asnita Sinaga; Agustina Susilawati Tumangger (Jurnal Medika Nusantara, 2024)
Hypertension or high blood pressure is a condition of increased pressure in the arteries. In general, hypertension often does not show symptoms, but blood pressure that is too high can increase the risk of stroke, aneurysm, heart failure, heart attack, and kidney damage. The purpose of this study was to analyze the effect of giving celery boiled water to the elderly with hypertension at the Rusip Health Center, Rusip Antara District, Central Aceh Regency, Aceh Province in 2022. The type of research is experimental with a research design using one group pre-post design, namely a research design that will be carried out by researchers by involving one group of subjects where the subject group will be observed before being treated and re-observed after being treated. This research was conducted at the Rusip Health Center, Rusip Antara District, Central Aceh Regency in 2022. The population in this study was 51 people, the number of samples used was 20 people using the Simple Random Sampling technique. The results of the study using the Wilcoxon test obtained a Z count value for systolic blood pressure of -2.911 with a p-value of 0.004. It is concluded that there is an effect of giving boiled celery water on reducing both systolic and diastolic blood pressure in elderly people with hypertension at the Rusip Health Center, Rusip Antara District, Central Aceh Regency in 2022.